Peningkatan Kemampuan Komunikasi Matematis Melalui Penerapan Model Pembelajaran Thinking Aloud Pair Problem Solving (TAPPS) Pada Siswa Kelas VIII MTs Bahrul Ulum - Nurin Rahmawati; Lusi Eka Afri; Marfi Ario (Program Studi Pendidikan Matematika Universitas Pasir Pengaraian, 2020)
This study aims to see whether or not there is an increase in mathematical communication skills by applying the Thinking Aloud Pair Problem Solving (TAPPS) learning model in class VIII students of MTs Bahrul Ulum. This research is a Quasi-Experimental study with the design of the randomized pretest-posttest control group design. The population in this study were all students of class VIII MTs Bahrul Ulum. The sample was taken by simple random sampling so that two classes were selected as the sample, namely class VIII C as the experimental class and class VIII D as the control class. The research instrument was a test item mathematical communication description. The data from the communication test results that have been obtained are then analyzed to test the hypothesis. Because the data were not normally distributed, then the hypothesis was tested using the Mann Whitney test. The calculation results showed that Zcount > Ztable, namely 3.226 > 1.96 for a = 0.05, then H0 was rejected. So it can be concluded that there is an increase in mathematical communication skills through the application of the Thinking Aloud Pair Problem Solving (TAPPS) learning model in class VIII students of MTs Bahrul Ulum in the 2019/ 2020 academic year.